2013
DOI: 10.2174/156652413804810781
|View full text |Cite
|
Sign up to set email alerts
|

Cell Death and Survival Through the Endoplasmic Reticulum- Mitochondrial Axis

Abstract: The endoplasmic reticulum has a central role in biosynthesis of a variety of proteins and lipids. Mitochondria generate ATP, synthesize and process numerous metabolites, and are key regulators of cell death. The architectures of endoplasmic reticulum and mitochondria change continually via the process of membrane fusion, fission, elongation, degradation, and renewal. These structural changes correlate with important changes in organellar function. Both organelles are capable of moving along the cytoskeleton, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 135 publications
(100 reference statements)
2
58
0
Order By: Relevance
“…Given that cardiac myocytes and skeletal myotubes have comparable levels of the mitochondria-associated protein MAVS (Figure 2C) but express significantly different basal levels of IFN-β (Figure 1B), MAVS abundance alone cannot be sufficient to drive spontaneous downstream signaling in cardiac myocytes. The mitochondria in cardiac myocytes are exceptionally well-associated with the sarcoplasmic reticulum (SR; the muscle-specific ER) to facilitate calcium (Ca 2+ ) transfer, reactive oxygen species (ROS) communication, and apoptotic signaling between these two organelles (10, 23, 26, 33). Our results suggest that the intrinsic association of the SR and mitochondria in cardiac myocytes likely facilitates the synthesis of basal IFN-β (Figures 3-4).…”
Section: Discussionmentioning
confidence: 99%
“…Given that cardiac myocytes and skeletal myotubes have comparable levels of the mitochondria-associated protein MAVS (Figure 2C) but express significantly different basal levels of IFN-β (Figure 1B), MAVS abundance alone cannot be sufficient to drive spontaneous downstream signaling in cardiac myocytes. The mitochondria in cardiac myocytes are exceptionally well-associated with the sarcoplasmic reticulum (SR; the muscle-specific ER) to facilitate calcium (Ca 2+ ) transfer, reactive oxygen species (ROS) communication, and apoptotic signaling between these two organelles (10, 23, 26, 33). Our results suggest that the intrinsic association of the SR and mitochondria in cardiac myocytes likely facilitates the synthesis of basal IFN-β (Figures 3-4).…”
Section: Discussionmentioning
confidence: 99%
“…1). Finally, it has been shown that the sGC-cGMP-PKG pathway regulates cytosolic Ca 2+ [101] and that mitofusion protein MFN2 is a crucial mediator of Ca 2+ flux between the mitochondria and ER [7174]. It is therefore interesting to speculate that Ca 2+ flux may be the downstream convergence point for these pathways and the currency for SMC phenotypic switching.…”
Section: Discussionmentioning
confidence: 99%
“…The transfer of calcium (Ca 2+ ) between mitochondria and ER is important for regulating mitochondrial bioenergetics and cell viability [7174]. The mitochondria-ER link promotes Ca 2+ flux into the mitochondria, an activity that is associated with increased ATP generation and anti-proliferative activity in SMC [75, 76].…”
Section: Mitochondrial Fusion and Smc Homeostasismentioning
confidence: 99%
“…The long-standing concept of mitochondria as free-floating cytoplasmic entities has been modified in the face of discovery that mitochondria interact via Bmembrane fusion, fission, elongation, degradation, and renewal[ with the endoplasmic reticulum (71). Indeed, mitochondria that are tethered to the ER create a mitochondria-associated endoplasmic reticulum membrane (MAM) junction, which is a focus for signaling.…”
Section: Mitochondria-associated Endoplasmic Reticulum Membrane and Errmentioning
confidence: 99%
“…Indeed, mitochondria that are tethered to the ER create a mitochondria-associated endoplasmic reticulum membrane (MAM) junction, which is a focus for signaling. Through this contact point, calcium and lipids are transferred, mediating communicating and signaling for both organelles (71,72).…”
Section: Mitochondria-associated Endoplasmic Reticulum Membrane and Errmentioning
confidence: 99%